Morphological abnormalities in cladocerans related to eutrophication of a tropical reservoir - de Melo, Rï¿½mulo R. R. (2017)
In zooplankton communities, morphological changes in Cladocera (Crustacea: Branchiopoda) may be resulting from water pollution by anthropogenic activities and/or natural events. The removal of vegetation cover, urbanization, agriculture and sewage release accelerate the eutrophication process in the aquatic environment. The present study seeks to demonstrate the occurrence of morphological abnormalities in cladocerans and relate the changes in the morphology and species composition to the physical and chemical parameters of the water. Samplings were made monthly in five stations on the Sapucaï¿½ River compartment of Furnas Reservoir, located in the state of Minas Gerais, Brazil, from July 2013 to February 2014.The Furnas Reservoir has intense occupation of the surrounding areas by agriculture, urban and industrial activities and the installation of net cage fish cultures, which contribute to the water quality deterioration. Cladocerans samples were collected using a suction pump and plankton net (68 μm mesh size) and concentrated from a volume of 400 L. The measures of physical and chemical parameters of the water were obtained by a Horiba U-50 multi-sensor on the surface of water column and the density and morphology of Cladocera were made by microscopy. Twenty-three species of Cladocera were recorded with high organism densities of Chydoridae family species. Morphological abnormalities were observed in Daphnia gessneri, Ceriodaphnia silvestrii, Bosmina longirostris, Bosmina tubicen and Chydorus pubescens. The highest densities of C. pubescens with abnormalities were observed at sampling stations which had littoral characteristics and influences of sewage release. For C. pubescens, abnormalities were observed and classified into two types. The type 1 abnormality was considered an increase of length of intestine and size of its intestinal loop, whereas for type 2 was considered the occurrence of an intestine prolapse. The morphological abnormalities in cladocerans were described and compared to the ones described in the literature. From the results, it may observe that the abnormalities were probably resulting from continuous eutrophication process which has been occurring in the reservoir due to anthropogenic activities around the reservoir and a decrease in the water volume of the reservoir, caused by an unusual dry weather period in this region in the last years.